STUDI HADITS PERGURUAN TINGGI MALAYSIA: PEMETAAN INSTITUSI, TREN PENELITIAN, METODOLOGI KAJIAN, DAN KONTRIBUSI AKADEMIK TERHADAP PERKEMBANGAN STUDI HADITS DI MALAYSIA - Aliyah Husna Ritonga; Nawir Yuslem; Asrar Mabrur Faza (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of Hadith studies in Malaysia has shown significant progress alongside the growth of Islamic higher education institutions as centers for education, research, and the advancement of Islamic scholarship. This article aims to analyze the evolution of Hadith studies in Malaysian higher education institutions by examining educational structures, research methodologies, research trends, and academic contributions to the field within Southeast Asia. A qualitative approach utilizing library research was employed. Data were gathered from diverse sources including books, journal articles, official institutional documents, and relevant scholarly publications and subsequently analyzed using content analysis techniques. The findings indicate that the International Islamic University Malaysia (IIUM), Universiti Malaya (UM), and Universiti Kebangsaan Malaysia (UKM) serve as key institutions in advancing Hadith studies through comprehensive curricula, innovative research, and high-quality scholarly publications. Evolving methodologies in the field encompass takhrij (tracing Hadith sources), the critique of sanad (chains of transmission) and matn (textual content), thematic (*maudhu'i*) approaches, and multidisciplinary methods linking Hadith studies with various other disciplines. Furthermore, research trends in Malaysia are increasingly shifting toward contextual studies that address issues related to education, law, health, psychology, and social life. The academic contributions of Malaysian institutionsevident in research productivity, scholarly output, international academic collaborations, and curriculum development have established Malaysia as a prominent hub for Hadith studies in Southeast Asia. This study is intended to serve as a reference for the further development of Hadith studies within Islamic higher education, particularly in the Southeast Asian region.